Where do we go? - Almirol, Brenner Aldreen P.
This study focuses on the behavior of rust when used as a medium in depicting a representational image. The depicted image is an assumed dystopia describing the disorder between nature and human. This dystopian image, being representational, has recognizable forms, and by the nature of rust being in constant change, it interacts with these recognizable forms, making the image fade. As a result, the process of rusting as it destroys the forms, serves as a metaphor for the disorder between nature and human. Further to that, the fading of forms continues as long as the process of rusting is at work. This translates to an even destruction of the image. And with that, the continual destruction of the image in an increasing efficiency conforms to the notion of increasing disorder, that is, entropy.